Literature and Language Learning in the EFL Classroom - Teranishi, Masayuki. author. aut Link
XXI, 329 p. 7 illus.
Keywords: This book examines how literary texts can be incorporated into teaching practices in an EFL classroom. It takes a multi-faceted approach to how English language teaching and learning can best be developed through presentation and exploration of literary texts.